SINTESIS PADUAN KOBALT MELALUI TEKNIK PELEBURAN DAN KARAKTERISASINYA SEBAGAI IMPLAN TULANG PROSTHESIS - Normasari Susanto, Efinda Putri; Indriani, Arista; Himawati, Umi; Aminatun, Aminatun (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Cobalt-based alloys are widely used to be prosthesis because of their excellent properties. In this work, cobalt alloys variation of Cr have been synthesized by smelting method and accompanied by rolling process. The evaluated material properties show that microstructure dominant by Î³ phase. It was also found that the whole process of synthesis have good solubility. Hardness value show variation of 33% Cr include on the range of ASTMF75 that is 345,24 VHN. Corrosion test result show variation of 31,5% and 34,5% Cr satisfy corrosion rate of Europe standard (0,457 mpy). But on the other hand, they have good biocompatibility.Keywords: Cobalt alloys prosthesis, microstructure, hardness value, corrosion rate, cytotoxicity.